Administration of White Turmeric (Curcuma zedoaria) Extract Increased Glutathion Peroxidase Levels and Reduced Malondialdehyde Mice (Mus musculus) Male Strain Balb/c That Were Exposed by Vehicle Fumes - Ana Yulia; I Wayan Weta; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Currently, air polution is a global health problem, including in Indonesia as developing country. Air pollution is known as oxidants and induces cell damage through the free radicals formation. In order to prevent oxidative stress due to exposure to air pollution, administration of exogenous antioxidants is necessary. White turmeric (Curcuma zedoaria) contains curcumin, tannin and polyphenols antioxidant activity may work to neutralize the effect that caused by air pollution. The aim of this study was to prove that supplementation of white turmeric extract increased glutathione peroxidase and decreased malondialdehyde in mice male strain Balb/c that were exposed by vehicles fumes. Methods: The randomized pretest-posttest control group design was conducted. The subjects 10 mice (strain Balb/c), male, age 2-3 months (adult mice), weight 20-22 grams, and healthy. Mice were divided into two groups (five mice each), namely the control and treatment group. Control group was given placebo of 2 ml aquabidest for 16 days and the treatment group was supplemented with white turmeric extract of 100 mg/kg BW for 16 days while exposed by motor vehicle fumes for those periode of time. Before and after treatment, Glutathion Peroxidase (GPx) and Malondialdehyde (MDA ) were measured using ELISA method. Results: Unpaired data comparison showed before the treatment (pretest), there were no differences in GPx levels (control 8.72±0.094, treatment 8,81±0,063, p= 0.114) and MDA levels (control 4,19±1,55, treatment 4,43±1,49, p= 0.812) between groups. While after treatment (posttest), the mean GPx levels (control 8.76±0.075, treatment 12.0±0.296; p <0.001) and MDA levels (control 2,.71±0.409, treatment 1.56±0.0019, p= 0.001) differed significantly Paired data analysis showed that in the control group there was a non-significant increase in GPx level (from 8.72±0.04 U to 8.76±0075 U; p=0.545), while in treatment group there was a significant increase in GPx levels (from 8.81 ± 0.063 U to 12.0 ± 0.296 U; p <0.001). In the control group there was a non-significant reduction in MDA level (from 4.19±1.55 U to 2,71±0.409 U; p=0.161, while in treatment group there was a significant reduction in MDA levels (from 4.43 ± 1.49 µM to 1.56 ± 0.326 µM; p= 0.019). Conclusion: Administration of white turmeric (Curcuma zedoaria) extract increased GPx levels and reduced mMDA in mice (Mus musculus) male strain Balb/c that were exposed by vehicles fumes.